Prática de exames preventivos, risco familiar e fatores associados ao câncer de mama: Inquérito de Saúde da Mulher em Uberaba - MG, 2014 - BURANELLO, Mariana Colombini (2016)
Worldwide, the most common type of cancer among women is breast cancer, corresponding 23% of all new cases. The main strategies in breast cancer control involve the primary and secondary prevention. The secondary prevention is composed of early detection actions, and these are the only ones capable of promoting reductions in mortality rates, receiving more attention of the health system. This research aims to: characterize the socioeconomic, epidemiological and health profile of women in Uberaba, according to the practice of preventive examinations for breast cancer and the risk of breast cancer by family history, as well as establish the prevalence of these outcomes; verify habits of preventive examinations for breast cancer among women according to age range in Uberaba; verify the association between the practice of preventive exams of breast cancer and income, education, risk by family history and personal history of general neoplasms and benign pleonasms of breast, age, type of mammography exam coverage, ethnicity, householder and marital status; verify the association of breast cancer occurrence according to risk by family history, physical activity, breast-feeding, nulliparity, obesity, aging and smoking. This research is part of a larger project, the Women's Health Survey in Uberaba MG (ISA - Woman), a transversal population-based study. For the evaluation of epidemiological and sociodemographic characteristics was used the identification block of general data, anthropometrics and physical activity (International Physical Activity Questionnaire - IPAQ). For the evaluation of preventive habits tests for breast cancer was used a questionnaire already used in other health surveys with the same goal. To determine the risk of developing breast cancer by family history was used the instrument Family History Screen 7 (FHS-7). The sample was composed for 1520 women over 20 years old living in Uberaba-MG. After processing the data, the statistical analysis was performed with association measures with the Chi Square test; analysis of bivariate and multivariate Poisson regression, with significance of 5%. The results showed a practice profile of preventive examinations for breast cancer composed by women of white ethnicity, education and income per capita higher, marital status "united", not households and non-smokers. The practice profile of preventive examinations revealed a higher prevalence realization of the clinical breast exam and mammogram for women between 50┤69 years old 40┤49 years old, with women of 70 years old or older who had the lowest prevalence of preventive habits. The factors associated with the higher prevalence of preventive examinations practice for breast cancer were the age range of 50┤69 years old and 40┤49 years old, per capita income higher than one minimum salary and coverage of public mammography exam or by health insurance. The prevalence of breast cancer occurrence in the studied sample was 0.47%. Just nulliparity variable was associated with the occurrence of breast cancer.